2018
DOI: 10.13031/aea.12461
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Diffuser Parameters for Mixing Fans in Agricultural Buildings

Abstract: Abstract. Mixing fans (MFFs) are widely used in ventilation of agricultural buildings to improve the uniformity of the air supply, thereby improving the ventilation efficiency. In order to improve the ventilation performance of MFFs, a new visor-shaped diffuser was designed and installed on a MFF. The angle and the length of the diffuser were crucial parameters that affected the performance of the MFFs with the diffusers. Thereby, in this study numerical simulation with 42 diffusers of different angles (ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this paper, the elevation angle of the fan diffuser was optimized by means of CFD simulation and laboratory prototype experiments. The CFD simulation of a prototype fan to obtain the jet length of the fan was successfully validated by [11]. Considering the interaction between the circumferential angle, the length, and the elevation angle of a diffuser, orthogonal tests were designed The RNG k-ε turbulence model of Fluent software (ANSYS CFX17.0, ANSYS, PA, USA) was used to study the turbulence model selection of low-pressure axial fans [11].…”
Section: Optimization Of the Geometric Parameters Of The Diffusermentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the elevation angle of the fan diffuser was optimized by means of CFD simulation and laboratory prototype experiments. The CFD simulation of a prototype fan to obtain the jet length of the fan was successfully validated by [11]. Considering the interaction between the circumferential angle, the length, and the elevation angle of a diffuser, orthogonal tests were designed The RNG k-ε turbulence model of Fluent software (ANSYS CFX17.0, ANSYS, PA, USA) was used to study the turbulence model selection of low-pressure axial fans [11].…”
Section: Optimization Of the Geometric Parameters Of The Diffusermentioning
confidence: 99%
“…Installing a diffuser in a fan is an effective means to optimize the aerodynamic performance of the fan [8][9][10]. In recent research on agricultural fans, it has been found that MFFs with a newly shaped diffuser have better performance than regular MFFs, with higher flow flux and energy efficiency because of the transformation of dynamic pressure into static pressure [11]. Considering a diffuser with a 150 • angle and 250 mm of length, the angle between the diffuser and the fan frame was optimized in this paper using CFD (Computational Fluid Dynamics) simulation and laboratory testing.…”
Section: Introductionmentioning
confidence: 99%